DC Fault Current Calculation Method and Transient Characteristics of True Bipolar MMC-HVDC Systems - Botong Li; Yichao Liu; Bin Li; Wenxin Wang; Weijie Wen; Xiaolong Chen (CSEE Journal of Power and Energy Systems)
In this paper, the calculation method and transient characteristics of asymmetric faults in the DC side of a true bipolar system are studied. First, two typical MMC fault equivalent methods are analyzed, and comparison shows that active RLC equivalent branches are more suitable for fault analyses of a true bipolar system. Second, considering the influence of mutual impedance between the poles in DC side, a DC fault current calculation method for a true bipolar systems is proposed. Finally, the characteristics of transient electrical quantities including fault current and DC voltage in the process of DC faults in true bipolar systems are analyzed and summarized to provide references for the design of DC line insulation and relay protection schemes.